2014
DOI: 10.1088/1367-2630/16/9/093002
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling hybrid diamond–biological quantum devices

Abstract: The realization of scalable arrangements of nitrogen vacancy (NV) centers in diamond remains a key challenge on the way towards efficient quantum information processing, quantum simulation and quantum sensing applications. Although technologies based on implanting NV-centers in bulk diamond crystals or hybrid device approaches have been developed, they are limited by the achievable spatial resolution and by the intricate technological complexities involved in achieving scalability. We propose and demonstrate a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 77 publications
(175 reference statements)
0
33
0
5
Order By: Relevance
“…For instance, nitrogen vacancy (NV) centers in diamonds have recently been shown to be strong candidates for use in the field of quantum technologies, with possible applications ranging from biological systems to quantum computing protocols [39]. Furthermore, for reducing the damage of environmental perturbations in NV centers, the CDD procedure has again proven to be very important [40].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nitrogen vacancy (NV) centers in diamonds have recently been shown to be strong candidates for use in the field of quantum technologies, with possible applications ranging from biological systems to quantum computing protocols [39]. Furthermore, for reducing the damage of environmental perturbations in NV centers, the CDD procedure has again proven to be very important [40].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that actin filament can be used as scaffold for building linear structures of NDs. Provided that we can optimize the size (ideally < 10 nm) of the diamond nanocrystals and the number of colour centres (ideally single NV centres) – which is not unrealistic for the current state‐of‐the art of diamond material science – our approach shows great promise towards the fabrication of quantum logic gates, memories and registers based on arrays of NV‐qubits and is an alternative to proposed DNA‐based assembly .…”
Section: Resultsmentioning
confidence: 99%
“…A new strategy based on self-assembly behavior of biological systems was applied to functionalized NDs [144]. Proteins can form 1D, 2D or 3D scaffolds on Fig.…”
Section: Patterning and Seedingmentioning
confidence: 99%